2021
DOI: 10.3390/ijerph182412924
|View full text |Cite
|
Sign up to set email alerts
|

Cafeteria Online: Nudges for Healthier Food Choices in a University Cafeteria—A Randomized Online Experiment

Abstract: Many people do not consume as much healthy food as recommended. Nudging has been identified as a promising intervention strategy to increase the consumption of healthy food. The present study analyzed the effects of three body shape nudges (thin, thick, or Giacometti artwork) on food ordering and assessed the mediating role of being aware of the nudge. Students (686) and employees (218) of a German university participated in an online experimental study. After randomization, participants visited a realistic on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…We adapted this nudge acceptance scale further by using the first eight types of nudges (messenger, incentive 1, incentive 2, norms, default, salience, priming, and affect) and added a ninth type (priming and salience). We added this ninth nudge because this type of nudge had been previously applied to the population of the present study in an online experiment [ 49 ]. In addition, a combination of priming and salience effects in nudging were found to be very effective [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adapted this nudge acceptance scale further by using the first eight types of nudges (messenger, incentive 1, incentive 2, norms, default, salience, priming, and affect) and added a ninth type (priming and salience). We added this ninth nudge because this type of nudge had been previously applied to the population of the present study in an online experiment [ 49 ]. In addition, a combination of priming and salience effects in nudging were found to be very effective [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a specific nudge that had been effectively applied to improve eating behavior in middle-aged samples was ineffective in young adults [ 48 ]. A similar healthy eating nudge applied in an online cafeteria setting was effective for employees but not for students [ 49 ]. The cause of these differential effects is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the Giacometti cue found it to effectively improve the dietary behavior of adults ranging between 35 and 39 years of age with a moderate effect size [30,32]. For young adults, the Giacometti cue was ineffective when applied in a virtual setting [53,57]. In the present study, the Giacometti cue had an immediate effect of reducing the number of calories purchased by university students in a real-world university cafeteria.…”
Section: Effects Of the Giacometti Cuementioning
confidence: 47%
“…At each counter on both cafeteria floors, we placed a DIN A5 poster of the sculpture called L'homme qui marche (Figure A2 in Appendix C). Both Giacometti cues had been previously used in other studies [15,30,[32][33][34]57]. They have been found to be effective when applied in different formats, such as a screensaver [30], a DIN A0 poster [33], and a small sticker [34].…”
Section: Methodsmentioning
confidence: 99%